Penyuluhan Menstruasi Sehat sebagai Upaya Mengatasi Mitos Pada Siswi Kelas V dan VI MI Nidhomiyah Jombang - Esti Pratiwi Yosin; Ratna Sari Dewi; Rista Novitasari; Dwi Anik Karya Setiarini (Pusat Penelitian dan Pengabdian Masyarakat STIKes Banyuwangi, 2026)
Background: Limited understanding of menstruation among elementary school girls is still frequently influenced by myths and inaccurate information, which negatively affects menstrual hygiene practices and fosters unfavorable perceptions of the menstrual process. Objective: This community service activity aimed to improve students’ knowledge of healthy menstruation as an effort to reduce the influence of myths through basic reproductive health education. Methods: The program was implemented through interactive educational sessions using booklets, distribution of leaflets, and knowledge evaluation using pre-test and post-test instruments among 52 fifth- and sixth-grade female students at MI Nidhomiyah Jombang. Results: The findings demonstrated a significant change in the level of understanding, marked by a shift from a predominance of poor knowledge before the intervention to a majority of students achieving a good level of knowledge after the intervention. Implications: These findings highlight the importance of integrating reproductive health education into regular school programs, with support from teachers and healthcare professionals, to ensure the sustainability of educational outcomes. Conclusion: This one-day educational activity was shown to contribute to improving students’ basic knowledge of menstruation and to reducing the influence of myths that may potentially interfere with reproductive health during early adolescence